Proceedings of Workshop on China Social Economics, Marketing and Policy of the Bamboo Sector, 16-18 June 1999, Beijing - Fu Maoyi; Ruíz Pérez, M.; Yang Xiaosheng (China Forestry Publishing House, 2001)
Over the past few years, a number of Chinese researchers have collaborated with CIFOR and INBAR/IDRC in a systematic, two-phase socio-economic study of the bamboo sector in China. This proceedings contains a synthesis from the main research findings from research programs related to socioeconomics, marketing and policy in the bamboo sector of China. The current status and planning in the main bamboo - growing regions and industry systems are addressed. The studies cover strategic objectives, major projects, planning and actions, as well as problems and countermeasures to remedy them. The directions of development and prospects for sustainable development of the bamboo sector into the 21st century are considered.